2017
DOI: 10.1002/jmv.24751
|View full text |Cite
|
Sign up to set email alerts
|

Viral pathogens among elderly people with acute respiratory infections in Shanghai, China: Preliminary results from a laboratory‐based surveillance, 2012‐2015

Abstract: Acute respiratory infections (ARIs), with viral pathogens as the major contributors, are the most common illnesses worldwide, and increase the morbidity and mortality among the elderly population. The clinical and pathological features of elderly people with ARIs need to be identified for disease intervention. This study identified influenza as the leading viral pathogen among elderly with ARIs, and two seasonal epidemic peaks were observed in Shanghai. An influenza vaccination strategy needs to be advocated f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 26 publications
2
17
0
Order By: Relevance
“…We found that the presence of fever remained important in the elderly to retain specificity for the diagnosis of influenza A(H3N2). This result is in agreement with those from previous studies [11,[29][30][31], in which fever was associated with influenza among older adults. The number of deaths was significantly associated with influenza A(H3N2)positive ARIs residents.…”
Section: Discussionsupporting
confidence: 93%
“…We found that the presence of fever remained important in the elderly to retain specificity for the diagnosis of influenza A(H3N2). This result is in agreement with those from previous studies [11,[29][30][31], in which fever was associated with influenza among older adults. The number of deaths was significantly associated with influenza A(H3N2)positive ARIs residents.…”
Section: Discussionsupporting
confidence: 93%
“…Additionally, in the last 15 years, newly discovered respiratory viruses have been identified including human metapneumovirus (HMPV), human bocavirus (HBoV), coronaviruses NL63 (HcoV‐NL63) and HKU1 (HcoV‐HKU1), new human enterovirus (HEV), human parechovirus (HPeV), and human rhinovirus (HRV) strains . Influenza is a well‐recognized cause of ARIs in adults but substantial adult disease is also caused by other respiratory viruses, particularly RSV and HMPV . Both viruses belong to the new family Pneumoviridae within order Mononegavirales, and have similar clinical features .…”
Section: Introductionmentioning
confidence: 99%
“…13 According to our previous study, influenza virus is the dominant pathogen among older people with acute respiratory infections in Shanghai. 14 This study aimed to assess the influenza VCR among older people in Shanghai during the 2016-17 influenza season and determine the reasons for vaccination or non-vaccination. The findings of this study are intended to provide scientific evidence for the implementation of appropriate strategies and programs targeting older people in Shanghai, and other developed areas with the potential condition for considering a subsidy policy for influenza vaccination.…”
Section: Introductionmentioning
confidence: 99%